ANKRD26 and Its Interacting Partners TRIO, GPS2, HMMR and DIPA Regulate Adipogenesis in 3T3-L1 Cells - Liu, Xiu-Fen (Public Library of Science, 2012)
Partial inactivation of the Ankyrin repeat domain 26 (Ankrd26) gene causes obesity and diabetes in mice and increases spontaneous and induced adipogenesis in mouse embryonic fibroblasts. However, it is not yet known how the Ankrd26 protein carries out its biological functions. We identified by yeast two-hybrid and immunoprecipitation assays the triple functional domain protein (TRIO), the G protein pathway suppressor 2 (GPS2), the delta-interacting protein A (DIPA) and the hyaluronan-mediated motility receptor (HMMR) as ANKRD26 interacting partners. Adipogenesis of 3T3-L1 cells was increased by selective down-regulation of Ankrd26, Trio, Gps2, Hmmr and Dipa. Furthermore, GPS2 and DIPA, which are normally located in the nucleus, were translocated to the cytoplasm, when the C-terminus of ANKRD26 was introduced into these cells. These findings provide biochemical evidence that ANKRD26, TRIO, GPS2 and HMMR are novel and important regulators of adipogenisis and identify new targets for the modulation of adipogenesis.